Review of Medicinal Applications, Phytochemistry and Pharmacological Properties of Aristea ecklonii - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Background: Aristea ecklonii is a perennial herb widely used as herbal medicine in southern Africa. Plants used as traditional medicines to treat various human diseases and illnesses play an important role in the primary healthcare of local communities in developing countries. Purpose: The current study critically reviewed the medicinal uses, phytochemistry and pharmacological properties of A. ecklonii. Methods: Literature on medicinal uses, phytochemical and pharmacological properties of A. ecklonii was collected from multiple internet sources including Elsevier, Google Scholar, SciFinder, Web of Science, Pubmed, BMC, Science Direct, and Scopus. Additional information was also obtained from pre-electronic sources such as books, book chapters, theses, scientific reports and journal articles obtained from the university library. Results: This study revealed that A. ecklonii is used as an ornamental plant, protective charm, and herbal medicine for internal sores, cough, fever, syphilis, shingles, and venereal diseases. Ethnopharmacological research identified quinones and sterols from leaves and rhizomes of A. ecklonii. The crude extracts of A. ecklonii and the compound plumbagin isolated from the species exhibited antibacterial and antifungal activities. Conclusion: Aristea ecklonii should be subjected to detailed phytochemical, pharmacological, and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological properties.